Relationship of Relactation with Mother's Breastfeeding in Sembung Village, Narmada District, West Lombok Regency - Ana Pujianti Harahap; Aulia Amini (Jurnal Kebidanan, 2023)
Exclusive breastfeeding can help babies achieve optimal growth, development and health. From the data obtained at the Indonesian Ministry of Health in 2017, the coverage of exclusive breastfeeding in the NTB region was 77%, still lagging behind the national coverage of 80%. The highest coverage is in the West Lombok Regency area of 95.8%. Relactation is an attempt to start breastfeeding again after some time has stopped. Relactation aims to change the attitude of mothers to breastfeed their babies again with breast milk. The purpose of this study was to determine the relationship between relactation and breastfeeding for breastfeeding mothers who have children aged 0-2 years in Sembung Village, Narmada District, West Lombok Regency, West Nusa Tenggara in 2020. The research design used in this study was descriptive-analytic with a cross approach. sectional. The population in this study were breastfeeding mothers, with the sample being breastfeeding mothers who had children aged 0-2 years. The number of samples is 30 people, and the sampling method is Purposive Sampling. The data analysis techniques used were univariate and bivariate using the Chi Square test. The results showed that most of the relactation of breastfeeding mothers who had children aged 0-2 years without tools was 24 respondents (80.0%) and breastfeeding was mostly disrupted by 16 respondents (53.3%). There is no statistically significant relationship between relactation and breastfeeding in breastfeeding mothers who have children aged 0-2 years (p value 0.855 > 0.05). Health workers should be able to provide support and motivation on an ongoing basis to be able to achieve successful relactation in breastfeeding mothers.